Peculiarities of ensuring the rights of the person during the pre-trial investigation of criminal offenses under the legislation of countries with Anglo-Saxon law - Bozhik, Valerij (ScienceRise: Juridical Science, 2021)
A review of the status of ensuring the rights of the individual during pre-trial investigations of criminal offences under foreign law has been carried out. It has been specified, that successful implementation of the model of the criminal offences optimum for Ukraine is possible on condition of detailed study of the foreign experience of functioning of this institution. An analysis was made of legislation and its application in the area of human rights during pre-trial investigations of minor criminal offences in countries with an Anglo-Saxon legal system. Attention was drawn to the fact that they differentiate between general and minor offences under the criminal law system. For minor offences, the so-called summary procedure is used. The main criterion for allocating proceedings for consideration by a court in summary proceedings is the degree of criminal risk of offences. It has been noted, that pre-trial investigations of minor offences in the United States follow the general procedure whereby an officer of the investigating authority makes an application for a warrant for the arrest of a person or for the search of the premises occupied by him/her, if there are grounds for doing so. The said statement is subject to verification and confirmation in the manner, on which the court may issue a warrant of arrest or search, which is in fact an indictment record of the commencement of official proceedings. Attention is drawn to the fact that, in cases, involving minor offences, arrest is generally not carried out - the accused is usually served with a summons to appear in court. Emphasised on the positive experience of England in the sphere of ensuring the rights of the individual in the proceedings of «non-arrest crime» by establishing in the law the grounds for detention of a person by the police without the order of a judge.